O abismo no uso da informática: quem são os incluídos e os excluídos do mundo digital? - PETROLI, Andressa (004, 2003)
O problema da exclusão digital se apresenta como um dos maiores desafios desse inicio de século com implicações diretas e indiretas sobre os mais variados aspectos de nossa sociedade moderna. A desigualdade registrada entre pobres e ricos entra agora na era digital e ameaça se expandir com a mesma rapidez da informática. Acredita-se que encarar o problema de frente, analisa-lo, entender suas causas e tentar prever suas consequências é a atitude mais coerente a ser tomada. Esta monografia apresenta aspectos gerais do problema da exclusão digital e esforços de sucesso na tentativa de sua redução no Brasil.

The problem of digital exclusion is presented as one of the biggest challenges in the befinning of this century, with direct and indirect implications on the most varied aspects of our modern society. The difference registered betweeen poor and rich people now enters in the digital age and threat to expand with same quickness to the information society. One believes that face the problem, to analyze it, to understand its causes and to try to foreseee its cosequences it is the most coherent attitude to be taken. This monograph presents general aspects of the digital exclusion problem and successful efforts in the attempt of its reducton in Brazil.
The abyss in the use of information technology: who are those included and excluded from the digital world?
Keywords: Inclusão digital; Informática; Informação e Comunicação